2019
DOI: 10.30972/bon.2823855
|View full text |Cite
|
Sign up to set email alerts
|

Estudio comparativo de plantas medicinales vinculadas a tradiciones indígenas y europeas en Uruguay

Abstract: Esta investigación presenta información etnobotánica sobre prácticas vinculadas al uso medicinal de plantas en poblaciones urbanas y rurales en los departamentos de Tacuarembó y Canelones, Uruguay. A través del método etnográfico, se realizaron entrevistas semi-estructuradas y de observación participante. A partir de los datos aportados por los entrevistados, se analizaron los conocimientos botánicos locales para su sistematización, comparando los diferentes usos medicinales, su variabilidad de uso en relación… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
1
6
0
1
Order By: Relevance
“…Our study revealed a wide diversity of species with various habits and uses that people maintain in their gardens or directly collect from nature, with a 50% component of native species. Comparing our findings with comprehensive studies on medicinal species in the northern region of the country (Castiñeira et al, 2018;Tabakian, 2019) there is significant overlap in introduced and numerous native species. However, some different species are notable, such as Schinus lentiscifolius, Aristolochia fimbriata, Anemia tomentosa, Ocimum carnosum, and Psidium salutare.…”
Section: Agrobiodiversity and Local Knowledgesupporting
confidence: 50%
See 2 more Smart Citations
“…Our study revealed a wide diversity of species with various habits and uses that people maintain in their gardens or directly collect from nature, with a 50% component of native species. Comparing our findings with comprehensive studies on medicinal species in the northern region of the country (Castiñeira et al, 2018;Tabakian, 2019) there is significant overlap in introduced and numerous native species. However, some different species are notable, such as Schinus lentiscifolius, Aristolochia fimbriata, Anemia tomentosa, Ocimum carnosum, and Psidium salutare.…”
Section: Agrobiodiversity and Local Knowledgesupporting
confidence: 50%
“…In addition, carbon sequestration, nutrient cycling, and water purification should be added to direct benefits. Medicinal species play a fundamental role in the health and daily life of rural communities in Uruguay (Prieto and Bustamante, 1996;Castiñeira et al, 2018;Tabakian, 2019). Our study revealed a wide diversity of species with various habits and uses that people maintain in their gardens or directly collect from nature, with a 50% component of native species.…”
Section: Agrobiodiversity and Local Knowledgementioning
confidence: 75%
See 1 more Smart Citation
“…Otras alternativas como el poder curativo de las plantas, los beneficios de la espiritualidad y la importancia de las familias en los procesos de manejo de la enfermedad (Tabakian, 2019;Velázquez & Jiménez, 2017;Galvis-Palacios, López-Díaz, & Florisa-Velásquez, 2019) se encuentran descritos en la literatura científica y empiezan a ser aceptados como necesarios para la prestación de los cuidados, especialmente en las familias campesinas. Dichos postulados toman importancia en especial si se busca desarrollar la interculturalidad y, en específico, la competencia cultural, con el fin último de mantener coherencia con los postulados de las ciencias de la salud, específicamente con enfermería y con los lineamientos políticos nacionales e internacionales.…”
Section: Discussionunclassified
“…Various studies support the popular therapeutic use of S. microstachya for the treatment of pain ( Table 1 and Table 2 ). The methanolic extract (3–30 mg/kg) and the flavonoid quercitrin (1–10 mg/kg) isolated from leaves and administered intraperitoneally, caused potent and dose-related analgesic effects, inhibiting abdominal constrictions induced by an injection of acetic acid in mice (mean ID50 = 7.9 and 2.4 mg/kg, respectively) [ 39 , 101 ]. This extract elicited antinociceptive action against other models of pain such as capsaicin- and formalin-induced licking and was able to reverse, in a dose-related manner, the mechanical hyperalgesia in the rat paw induced by carrageenan, capsaicin, substance P, bradykinin and adrenaline [ 101 ].…”
Section: Biological Activitymentioning
confidence: 99%